Порівняльний аналіз рівня довіри громадян ЄС до наднаціональних політичних інституцій - Малигін, О.В.; Malygin, O.V. (Східноєвропейський національний університет імені Лесі Українки, 2013)
This paper compares the confidence level EU citizens to supranational institutions in the context of two groups - the "old democracies" countries and the countries that joined the EU after 2004. It examines the influence Corruption Perception Index on trust to EU supranational institutions.
Comparative analysis confidence level EU citizens to supranational political institutions
О.В. Малигін, к.т.н., доц. кафедри міжнародної інформації Хмельницького національного університету (Україна, м.Хмельницький)
Keywords: trust; EU; supranational institutions; correlation; corruption